FESTIVAL CIKAR SEBAGAI BUDAYA LOKAL MASYARAKAT KECAMATAN AMBULU KABUPATEN JEMBER TAHUN 1989-2018 - Maulana, Moh Ishaq (History Department, Faculty of Humanities, University of Jember, 2024)
This article discusses the Cikar Festival as a Local Culture of the People of Ambulu District, Jember Regency, 1989-2018. The purpose of this paper is to find out the history of the beginning of the Cikar Festival in Ambulu Subdistrict, what efforts have been made by the community and the government to preserve the Cikar Festival, and to know the development of the Cikar Festival in 1989-2018. This research uses historical methods to uncover the problems that are being studied. This festival originated from the habits of the owners of the cikar in Ambulu Subdistrict, who traveled to Watu Ulo Beach, which is held at every Lebaran Ketupat celebration. In 1989 these activities began to be contested by several Ambulu people. This is evidenced by establishing the Margo Rukun Association, as a forum for cikar artisans to preserve these activities to be more coordinated. Cikar itself is a traditional transportation tool in the form of a cart pulled by two adult cows, which some people in Ambulu District still use. The dynamics related to the reduction in the number of cikar participants are due to the decreasing number of cikar owners and the progress of an increasingly modern era. The significant reduction in the number of participants in the Cikar festival in 2018 made the government not remain silent. So that year the Regent of Jember and the Department of Tourism and Culture of Jember Regency (Disparbud) who were present at the festival made an effort to keep the cikar at Ambulu holding this festival every year and strive for the Cikar festival to become one of the cultural icons in Jember. Keywords: Transportation; Tradition; Festival